Bilateral intra-industry trade flows and intellectual property rights protections: further evidence from the United Kingdom. Issue 4 (19th May 2018) - Hasim, Haslifah M.; Al-Mawali, Nasser; Das, Debojyoti
ABSTRACT: This paper investigates the relationship between the United Kingdom's (hereafter referred as UK) bilateral intra-industry trade (IIT) and foreign intellectual property rights (IPRs) protections. The empirical investigation is based on pooled UK data and benefits from the theoretical distinction between horizontal and vertical IIT. It also estimates a gravity equation for international trade using both fixed and random effects models. We then extend the analysis by employing the GMM system for dynamic panel models. The principal findings suggest that the UK's IIT is stimulated when the level of a trading partner's IPRs and its imitative ability are considered jointly. However, when IPRs and imitation abilities are considered separately, their disparate effects are not an important factor in determining UK IIT flows.